Service Request Approach for e-Governance using Federation of Cloud - Gupta, Ashutosh; Dhyani, Praveen; Rishi, OP; Pathak, Vishwambhar (International Journal of Computer Sciences and Engineering, 2025)
Job scheduling is one of the major task in the federated cloud computing environment. In this paper a method using the existing job sequencing with deadline algorithm is proposed. The presented model including the existing job sequencing with deadline algorithm, sequences the jobs according to the optimization criterion of minimum energy consumption by the data center server, with the constraint to complete the jobs within deadline. The study mainly emphasizes to develop a system that maximizes the utilization of computing resources on one hand, while on other hand provides proper load balancing and task scheduling to get the optimal solution in the cloud federation for e-Governance services.